2016
DOI: 10.1002/ccr3.618
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity due to zinc phosphide poisoning in two patients: role of N‐acetylcysteine

Abstract: Key Clinical MessageZinc phosphide (Zn3P2/ZnP) is used as a rodenticide. The most common signs of toxicity are nausea, vomiting, hypotension, and metabolic acidosis; patients presenting such signs are referred to the emergency department (ED) of the hospitals. Therefore, this study aimed to report two cases of hepatotoxicity following accidental and intentional ZnP poisoning and successful management with N‐acetylcysteine (NAC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Consistent with our findings, previous studies have shown that the most common clinical signs of AlP and ZnP poisoning include vomiting, abdominal pain, palpitation, dyspnea, tachypnea, metabolic acidosis, shock, and hypotension. Furthermore, studies have indicated that hepatic enzymes might increase during poisoning (6,15). The most important dissimilarity of ZnP and AlP poisoning is the relatively longer time of symptom appearance upon poisoning by ZnP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent with our findings, previous studies have shown that the most common clinical signs of AlP and ZnP poisoning include vomiting, abdominal pain, palpitation, dyspnea, tachypnea, metabolic acidosis, shock, and hypotension. Furthermore, studies have indicated that hepatic enzymes might increase during poisoning (6,15). The most important dissimilarity of ZnP and AlP poisoning is the relatively longer time of symptom appearance upon poisoning by ZnP.…”
Section: Discussionmentioning
confidence: 99%
“…It can change into cysteine or mercaptate conjugates in acetaminophen (N-acetyl-p-benzoquinone imine) or poisoning due to mercury consumption. Therefore, many poisoned patients, who are treated with NAC, do not show hepatotoxicity and are only hospitalized for a short period (6,16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metal phosphides such as aluminum phosphide and zinc phosphide (Zn 3 P 2 ) are among the most potent rodenticides. In both humans and rodents, gastric acid reacts with phosphide to generate toxic phosphine gas, a highly lethal compound .…”
Section: Introductionmentioning
confidence: 99%